Liraglutide Inhibits Osteoclastogenesis and Improves Bone Loss by Downregulating Trem2 in Female Type 1 Diabetic Mice: Findings From Transcriptomics - Yu, Jie; Shi, Yan-Chuan; Ping, Fan; Li, Wei; Zhang, Hua-Bing; He, Shu-Li; Zhao, Yuan; Xu, Ling-Ling; Li, Yu-Xiu (Frontiers in Endocrinology, 2021)
Background The mechanisms of bone fragility in type 1 diabetes (T1D) are not fully understood. Whether glucagon-like peptide-1 receptor (GLP-1R) agonists could improve bone quality in T1D context also remains elusive. Aims We aimed to explore the possible mechanisms of bone loss in T1D and clarify whether liraglutide has effects on bone quality of T1D mice using transcriptomics. Methods Female streptozotocin-induced diabetic C57BL/6J mice were randomly divided into four groups and received the following treatments daily for 8 weeks: saline as controls, insulin, liraglutide, and liraglutide combined with insulin. These groups were also compared with non-STZ-treated normal glucose tolerance (NGT) group. Trunk blood and bone tissues were collected for analysis. Three tibia from each of the NGT, saline-treated, and liraglutide-treated groups were randomly selected for transcriptomics. Results Compared with NGT mice, saline-treated T1D mice manifested markedly hyperglycemia and weight loss, and micro-CT revealed significantly lower bone mineral density (BMD) and deficient microarchitectures in tibias. Eight weeks of treatment with liraglutide alone or combined with insulin rescued the decreased BMD and partly corrected the compromised trabecular microarchitectures. Transcriptomics analysis showed there were 789 differentially expressed genes mainly mapped to osteoclastogenesis and inflammation pathways. The RT-qPCR verified that the gene expression of Trem2, Nfatc1, Trap, and Ctsk were significantly increased in the tibia of T1D compared with those in the NGT group. Liraglutide treatment alone or combined with insulin could effectively suppress osteoclastogenesis by downregulating the gene expression of Trem2, Nfatc1, Ctsk, and Trap. Conclusions Taken together, increased osteoclastogenesis with upregulated expression of Trem2 played an important role in bone loss of T1D mice. Liraglutide provided protective effects on bone loss in T1D mice by suppressing osteoclastogenesis.